2010
DOI: 10.1111/j.1742-1241.2010.02484.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use in England: results from a national survey

Abstract: Summary Objectives:  In many countries, recent data on the use of complementary and alternative medicine (CAM) are available. However, in England, there is a paucity of such data. We sought to determine the prevalence and predictors of CAM use in England. Design:  Data were obtained from the Health Survey for England 2005, a national household survey that included questions on CAM use. We used binary logistic regression modelling to explore whether demographic, health and lifestyle factors predict CAM use. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
176
2
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(204 citation statements)
references
References 19 publications
15
176
2
11
Order By: Relevance
“…85 The participants included patients with asthma, 26 The use of a random-sampling method was mentioned in 13 (14.6%) surveys. 2,7,16,20,24,26,31,34,44,55,58,64,65 The response rates ranged from 13.8% to 100% (average 69.7%). Across surveys on CAM in general, the average one-year prevalence was 41.1% (range 9.2-100%) and the average lifetime prevalence was 51.8% (range 29-71%).…”
Section: Resultsmentioning
confidence: 99%
“…85 The participants included patients with asthma, 26 The use of a random-sampling method was mentioned in 13 (14.6%) surveys. 2,7,16,20,24,26,31,34,44,55,58,64,65 The response rates ranged from 13.8% to 100% (average 69.7%). Across surveys on CAM in general, the average one-year prevalence was 41.1% (range 9.2-100%) and the average lifetime prevalence was 51.8% (range 29-71%).…”
Section: Resultsmentioning
confidence: 99%
“…The herbal medicine, acupuncture and massage therapy are most commonly in young adult and adults in US [16,17] . In UK, massage, aromatherapy, herbal medicine and acupuncture were the most commonly used [18] . The differences on types of UM used by young adults in different countries due to the young adults can influence by several factors included individual and social and culture influencing factors [19] .…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, in 2005 the Health Survey of England reported a 26 per cent prevalence of CAM use in the last 12 months. Internationally the figure is higher with 12 month prevalence of CAM use reported as 62 per cent, 69 per cent and 76 per cent in the Germany, Australia and Japan (Hunt et al 2010). In the United States, Eisenberg et al found that between 1990 and 1997 the total visits to alternative medical practitioners (defined as a specific list of 16 therapies) had increased by 47 per cent from 427 million to 629 million, thereby exceeding total visits to all US primary care physicians (Eisenberg et al 1998).…”
Section: Countrymentioning
confidence: 99%